Assessment of species limits in African 'brown buntings' (Emberiza, Passeriformes) based on mitochondrial and nuclear sequence data. (8th June 2013) - Olsson, Urban; Yosef, Reuven; Alström, Per; Collinson, Martin
<x xml:space="preserve">Abstract</x> We estimated a phylogeny for 10 taxa currently placed in four polytypic species that collectively encompass the African 'brown buntings': Cape Bunting Emberiza capensis, Cinnamon‐breasted Bunting Emberiza tahapisi, Lark‐like Bunting Emberiza impetuani and House Bunting Emberiza striolata. We made use of the mitochondrial cytochrome b gene and the nuclear introns 6–7 of ornithine decarboxylase (ODC), and intron 2 of myoglobin. There was substantial cytochrome b sequence divergence between taxa currently treated as conspecific: sahari vs. striolata (2.6–3.1% (uncorrected‐p); 3.0–3.6% (HKY + I)), and goslingi vs. tahapisi (4.4–4.7% (uncorrected‐p); 5.4–5.9% (HKY + I)). The degree of divergence of the nuclear loci among taxa was limited, and these loci lacked reciprocal monophyly, most likely as a consequence of incomplete lineage sorting. A single representative of the taxon septemstriata, generally treated as a member of the dark‐throated tahapisi group, here appears to be genetically consistent with the grey‐throated goslingi, and may be of hybrid origin. All other taxa allocated to E. striolata and E. tahapisi make up four reciprocally monophyletic groups consistent with sahari, striolata, tahapisi and goslingi, respectively. The extent of genetic evidence suggests that these taxa have been evolving as separate evolutionary lineages for a long time. This is further manifested in several morphological and vocal characteristics described previously, and we propose that these divergent taxa be treated as separate species: Cinnamon‐breasted Bunting Emberiza tahapisi, Gosling's Bunting Emberiza goslingi, Striolated Bunting Emberiza striolata and House Bunting Emberiza sahari. We do not propose any taxonomic changes regarding Emberiza impetuani or Emberiza capensis.